Optimization of the nutrition area of an apple garden as a factor of intensification of fruit production - Namozov Ikhtiyor Choriyevich; Khurramov Ulugbek Kholmamatovich (Research Parks Publishing LLC, 2020)
The scientific article provides experimental material on the result of a study on the influence of the distribution scheme of spore apple varieties grafted on a dwarf rootstock of apple tree M-IX. Studies have established that in the juvenile period of development of the distribution scheme, the development of young trees does not significantly affect. Starting from 5-6 years of age, the influence of this factor manifests itself significantly in the thickening of the crown of trees. During this period, in order to maintain a stable volume of the crown and the level of illumination, it is necessary to thin out the shoots in the crown of trees, combining with moderate shortening of large branches. In order to increase productivity, the Fuji apple variety should be placed according to the 4x1 meter scheme, Golden Delicious 4x1.5 meters.